Inclusion in school dance teaching (Research, Society and Development, 2020)
This review text aims to dialogue about inclusion in the teaching of educational dance. Daily conflicts in aesthetic, didactic, relational and cultural aspects. The article was developed by the authors' work experience in line with the theoretical support of a study that verified the factors of obesity in dance teaching at school, by Lima (2016). The clipping of the bibliographic survey dealt with the concepts of educational dance, body image and social inclusion. We highlight the concepts of dance in school, the context of educational dance, the challenges of teaching for all students, for all bodies and physical constitutions, including the conception of body image of dancing bodies. We consider that educational dance is a branch of dance that is an improvement of the artistic, human and social formation of the students. However, the exclusionary features of dance at school are closely related to the world view of the school community and how prejudice is addressed.